Cite right : - Lipson, Charles (University of Chicago Press, 2006)
In his bestselling guide, Doing Honest Work in College: How to Prepare Citations, Avoid Plagiarism, and Achieve Real Academic Success, veteran teacher Charles Lipson brought welcome clarity to the principles of academic honesty as well as to the often murky issues surrounding plagiarism in the digital age. Thousands of students have turned to Lipson for no-nonsense advice on how to cite sources properly - and avoid plagiarism - when writing their research papers. With his latest book, Cite Right, Lipson once again provides much-needed counsel in a concise and affordable handbook for students and researchers. Building on Doing Honest Work in College, Lipson's new book offers a wealth of information on an even greater range of citation styles and details the intricacies of many additional kinds of sources. Lipson's introductory essay, "Why Cite," explains the reasons it is so important to use citations (and to present them accurately) in research writing. In subsequent chapters, Lipson explains the main citation styles students and researchers are likely to encounter in their academic work: Chicago; MLA; APA; CSE (biological sciences); AMA (medical sciences); ACS (chemistry, mathematics, and computer science); physics, astrophysics, and astronomy; Bluebook and ALWD (law); and AAA (anthropology and ethnography). His discussions of these styles are presented simply and clearly with examples drawn from a wide range of source types crossing all disciplines, from the arts and humanities to science, law, and medicine.